ÓSPIRIMLERDE DEPRESSIYA JAǴDAYÍ HÁM ONÍŃ JÚZEGE KELIW SEBEPLERI - Saparov, Sh.; Mambetnazarova, M. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the reasons of coming up of depression in teenagers and its psycho-prophylactical measures. In the article several methods were used for studying degrees of depression in teenagers. The results are based on the analysis.
Keywords: depression; youth; affect; emotion; psychodiagnostics; communication; motivation